The Impact of Applying the Breast Crawl (TBC) with other Educational Strategies on Breastfeeding Self-Efficacy after the First Breastfeeding among Primiparous Women in Dezful - Fereshteh Abdollahipour; Sadigheh Nouhjah; Seyed Mahmood Latifi; Marzieh Araban (Iranian Association of Health Education and Health Promotion, 2017)
Background and objective: Breastfeeding self-efficacy could be a strong predictive factor in breastfeeding. The aim of this study was to compare the impact of breastfeeding self-efficacy applying TBC (crawling baby to the mother's breast) and other self-efficacy promoting strategies after the first breastfeeding in primiparous women admitted to the maternity ward of Ganjavian hospital in the city of Dezful, Khuzestan Province, Iran. Materials and methods: In this quasi-experimental study, the sample size was 120 primiparous pregnant women admitted to the maternity ward of Ganjavian hospital in Dezful. Eligible individuals with consent were enrolled in the study. Participants completed a five-part pre-test questionnaire prior to childbirth. After childbirth, subjects were randomly divided into two intervention groups and one control group. Post-test was taken by breastfeeding self-efficacy questionnaire during the first 24 hours after delivery. For data analysis, descriptive statistics and ANOVA were used through SPSS 16. Significant correlation was considered as p < 0.05. Results: Breastfeeding self-efficacy scores increased in all three groups. But only the intervention group based on educational strategies showed a statistically significant compared to the control group (p = 0.039). The breast crawl (TBC) group showed no statistically significant (p = 0.076) compared with other groups (p = 0.990). Conclusion: Due to the many advantages of TBC, besides educating based on self-efficacy promoting strategies, TBC is also recommended for primiparous Paper type: Research Article.